Direct High‐Throughput Screening Assay for mRNA Cap Guanine‐N7 Methyltransferase Activity. Issue 49 (10th August 2020) - Kasprzyk, Renata; Fido, Mateusz; Mamot, Adam; Wanat, Przemyslaw; Smietanski, Miroslaw; Kopcial, Michal; Cowling, Victoria H.; Kowalska, Joanna; Jemielity, Jacek
Abstract: In eukaryotes, mature mRNA is formed through modifications of precursor mRNA, one of which is 5' cap biosynthesis, involving RNA cap guanine‐N7 methyltransferase (N7‐MTase). N7‐MTases are also encoded by some eukaryotic viruses and facilitate their replication. N7‐MTase inhibitors have therapeutic potential, but their discovery is difficult because long RNA substrates are usually required for activity. Herein, we report a universal N7‐MTase activity assay based on small‐molecule fluorescent probes. We synthesized 12 fluorescent substrate analogues (GpppA and GpppG derivatives) varying in the dye type, dye attachment site, and linker length. GpppA labeled with pyrene at the 3'‐O position of adenosine acted as an artificial substrate with the properties of a turn‐off probe for all three tested N7‐MTases (human, parasite, and viral). Using this compound, a N7‐MTase inhibitor assay adaptable to high‐throughput screening was developed and used to screen synthetic substrate analogues and a commercial library. Several inhibitors with nanomolar activities were identified. Abstract : Methyltransfer erasers : m 7 G cap biosynthesis is an important step in mRNA maturation, involving mRNA cap guanine‐N7 methyltransferase, which is a potential target for antiviral and anticancer therapies. This is the first report of a direct HTS, fluorescence‐based method for monitoring of the N7‐methylation process and the selection of specific N7‐methyltransferase inhibitors.